Pengaruh Takwa Terhadap Efektivitas Problem Solving - Iis Aisyah; Ripaul Husna; Abdul Ghoni (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Problems are one thing that cannot be separated in human life which requires us to face and solve them every day. In living their lives as servants of Allah swt, humans are often faced with various problems. Problems can be understood as one part of every struggle that cannot be avoided by every human being. Every problem sometimes feels very heavy, so many humans feel very miserable when they get problems. This study aims to see how piety affects the effectiveness of problem solving. The results showed that piety had an effect of 25.7% on the effectiveness of problem solving with a significant positive correlation (P < 0.05). This study shows a significant influence between the level of piety and problem solving ability. With a percentage Individuals who have a high level of piety tend to be better able to face and solve problems better. The aspects of piety that contribute the most to problem solving ability are mental resilience, patience, sincerity in trying, and full trust in Allah after making maximum effort. The research method used is mixed methods, which combines qualitative research taken from the book of tafsir, papers, and journals related to the theme, and quantitative methods taken from the results of distributing questionnaires and then processed using the methodology used in this study.